2007
DOI: 10.1113/jphysiol.2007.144519
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin selectively inhibits oxytocin neurons of the paraventricular nucleus of the hypothalamus

Abstract: Adiponectin is an adipocyte derived hormone which acts in the brain to modulate energy homeostasis and autonomic function. The paraventricular nucleus of the hypothalamus (PVN) which plays a key role in controlling pituitary hormone secretion has been suggested to be a central target for adiponectin actions. A number of hormones produced by PVN neurons have been implicated in the regulation of energy homeostasis including oxytocin, corticotropin releasing hormone and thyrotropin releasing hormone. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 55 publications
1
54
0
5
Order By: Relevance
“…Treatment with ADP lowers hepatic gluconeogenesis, serum glucose and ameliorates insulin resistance in mice [40][41][42][43]. Recent studies demonstrating that microinjection of ADP into the cerebral ventricles of mice also caused changes in glucose, lipid handling, and body weight have identified the brain and the PVN in particular as a potentially important target for ADP actions [44].Two different adiponectin receptors have been identified, adipoR1 and adipoR2 [40], and we have confirmed expression of adiponectin receptors in the PVN and also have identified direct hyperpolarizing effects of adiponectin on magnocellular oxytocin secreting neurons in the PVN, cells which also express mRNA for both adiponectin receptors (shown using single cell RTPCR) [45]. In contrast, we have also obtained preliminary data showing depolarizing effects of adiponectin on parvocellular CRH and TRH neurons in hypothalamic slices (again identified using single cell RTPCR) and have correlated these observations with data from conscious animals showing that intracerebroventricular adiponectin also increases plasma ACTH concentrations (Hoyda et al -unpublished).…”
Section: 13mentioning
confidence: 55%
“…Treatment with ADP lowers hepatic gluconeogenesis, serum glucose and ameliorates insulin resistance in mice [40][41][42][43]. Recent studies demonstrating that microinjection of ADP into the cerebral ventricles of mice also caused changes in glucose, lipid handling, and body weight have identified the brain and the PVN in particular as a potentially important target for ADP actions [44].Two different adiponectin receptors have been identified, adipoR1 and adipoR2 [40], and we have confirmed expression of adiponectin receptors in the PVN and also have identified direct hyperpolarizing effects of adiponectin on magnocellular oxytocin secreting neurons in the PVN, cells which also express mRNA for both adiponectin receptors (shown using single cell RTPCR) [45]. In contrast, we have also obtained preliminary data showing depolarizing effects of adiponectin on parvocellular CRH and TRH neurons in hypothalamic slices (again identified using single cell RTPCR) and have correlated these observations with data from conscious animals showing that intracerebroventricular adiponectin also increases plasma ACTH concentrations (Hoyda et al -unpublished).…”
Section: 13mentioning
confidence: 55%
“…AdipoR1 and AdipoR2 receptors are widely distributed throughout the central nervous system (CNS), with expression detected in regions of the hypothalamus and brainstem that are involved in the control of feeding behavior and energy expenditure [181,182,187]. Moreover, it was recently demonstrated that adiponectin can influence the excitability of different groups of neuron in the paraventricular nucleus, including neuroendocrine-CRH, preautonomic-TRH and preautonomic-oxytocin neurons [188].…”
Section: Central Nervous System and The Pituitary Glandmentioning
confidence: 99%
“…area postrema and paraventricular nuclei neurons [11, 14, 27, 28] and murine brain endothelial cells [15], as well as in human brain whole extracts [11, 19]. Furthermore, adiponectin receptor mRNA has been documented in rat and human pituitary extracts [23, 26].…”
Section: Introductionmentioning
confidence: 99%